1995
DOI: 10.1200/jco.1995.13.7.1777
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal doxorubicin: antitumor activity and unique toxicities during two complementary phase I studies.

Abstract: The toxicity profile of DOX-SL differs prominently from that of the free drug administered by bolus or rapid infusion and with some differences, resembles that of prolonged continuous infusion. This finding, as well as the antitumor activity observed, supports wide phase II testing of DOX-SL in solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
218
1
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(224 citation statements)
references
References 22 publications
3
218
1
1
Order By: Relevance
“…Mucositis was also rare and mild. No infusionrelated reactions, which are sometimes seen in cases of liposomal drug administration (Uziely et al, 1995;Muggia et al, 1996;Stewart et al, 1998;Gordon et al, 2001), occurred in this trial. Ultimately, this phase I study showed that the recommended dosage of NK911 (50 mg m À2 ) using a 3-week schedule was similar to the recommended dosage of free DXR (40 -60 mg m À2 ).…”
Section: Discussionmentioning
confidence: 66%
“…Mucositis was also rare and mild. No infusionrelated reactions, which are sometimes seen in cases of liposomal drug administration (Uziely et al, 1995;Muggia et al, 1996;Stewart et al, 1998;Gordon et al, 2001), occurred in this trial. Ultimately, this phase I study showed that the recommended dosage of NK911 (50 mg m À2 ) using a 3-week schedule was similar to the recommended dosage of free DXR (40 -60 mg m À2 ).…”
Section: Discussionmentioning
confidence: 66%
“…Phase I trials of SL-DOX have indicated that SL-DOX has activity in breast, ovarian, head and neck, prostatic, renal cell and non-smallcell lung carcinomas (Uziely et al, 1995).…”
Section: Results Patientsmentioning
confidence: 99%
“…Dose-limiting toxicities of PLD include reversible neutropaenia, stomatitis and plantar-palmar erythrodysaesthesia. Alopecia and emesis are infrequent (Uziely et al, 1995). A phase I study in 33 patients with advanced HCC determined neutropaenia as the doselimiting toxicity at 60 mg m À2 and recommended 50 mg m À2 every 28 days as the phase II dosing regimen (Schering Plough -data on file).…”
mentioning
confidence: 99%